Genome-wide identification and analysis of the regulation wheat DnaJ family genes following wheat yellow mosaic virus infection - Ting-ting LIU; Miao-ze XU; Shi-qi GAO; Yang ZHANG; Yang HU; Peng JIN; Lin-na CAI; Ye CHENG; Jian-ping CHEN; Jian YANG; Kai-li ZHONG (Journal of Integrative Agriculture, 2022)
The co-chaperone DnaJ plays an important role in protein folding and regulation of various physiological activities, and participates in several pathological processes. DnaJ has been extensively studied in many species including humans, drosophila, mushrooms, tomatoes, and Arabidopsis. However, few studies have examined the role of DnaJ in wheat (Triticum aestivum), and the interaction mechanism between TaDnaJs and plant viruses. Here, we identified 236 TaDnaJs and performed a comprehensive genome-wide analysis of conserved domains, gene structure and protein motifs, chromosomal positions and duplication relationships, and cis-acting elements. We grouped these TaDnaJs according to their domains, and randomly selected six genes from the groups for tissue-specific analysis, and expression profiles analysis under hormone stress, and 17 genes for plant virus infection stress. In qRT-PCR, we found that among the 17 TaDnaJ genes tested, 16 genes were up-regulated after wheat yellow mosaic virus (WYMV) infection, indicating that the TaDnaJ family is involved in plant defense response. Subsequent yeast two-hybrid assays verified the WYMV NIa, NIb and 7KD proteins interacted with TaDJC (TraesCS7A02G506000), which had the most significant changes in gene expression levels after WYMV infection. Insights into the molecular mechanisms of TaDnaJ-mediated stress tolerance and sensitivity could inform different strategies designed to improve crop resistance to abiotic and biotic stress. This study provides a basis for future investigation of the TaDnaJ family and plant defense mechanisms.